(untitled) (Annals of Medical Research, 2022)
Aim: Asthma and allergic rhinitis (AR) are chronic disorders that occur frequently and affect the quality of life. It is important to identify aeroallergens in a certain region to diagnose and treat asthma and AR in susceptible persons. We aimed to determine the distribution of aeroallergen sensitization rates using the skin prick test (SPT) in adult patients with AR and/or asthma in Malatya Province, Turkey. Materials and Methods: Between May 2018 and December 2021, we retrospectively reviewed the data of patients with AR and/or asthma and sensitivity to at least one aeroallergen on the SPT. Results: Of the 419 patients enrolled in our study, 334 (79.7%) had only AR, 68 (16.2%) had both AR and asthma, and 17 (4.1%) had only asthma. A total of 259 (61.8%) patients were women, and the mean age was 30.52 ± 10.06 years. Sensitization to grass mix was most common (71.8%), and its rate was higher among patients with only AR and those with AR and asthma (75.1% vs. 64.7%, p = 0.001) than in patients with only asthma. However, the sensitization rate to Dermatophagoides pteronyssinus was higher in patients with only asthma (47.1%, p < 0.001) than in the other groups. Conclusion: We found that grass mix was the most common sensitizing aeroallergen in accordance with the geographic and climatic characteristics of Malatya Province. This information may help with diagnosis, management, and prevention of AR and asthma.